Incidencia jurídica por la ausencia del fiscal a la audiencia oral de fundamentación del dictamen fiscal y preparatoria de juicio en el cantón Huaquillas, durante el periodo 2011-2012. Propuesta de reforma jurídica al segundo innumerado del Art. 226 del código de procedimientos penal. - Preciado Román, Ingrid Doménica (2013)
At present, the criminal procedural system requires certain legal reforms so that in accordance with the 2008 Constitution, it can effectively guarantee due process. That is why we have seen the need to investigate a factor that is somehow hindering an effective and effective criminal process, and is that the prosecutor or fiscal agent not being able to attend the hearing preparatory to trials and formulation of the tax bill, Obliged to restate a date to take effect.